Die Epermeniidae der äthiopischen Region (Lepidoptera). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1976)
Of the nine species known so far from the region of Ethiopia, three could be studied. On species described as Scythris belongs to the genus Epermenia, a species discribed as Epermenia belongs to the genus Ochromolopis. Nomenclatural Actsphiloritis (Bradley, 1965) (Epermenia (Calotripis)), comb. n. hitherto Scythris philoritispraefumata (Meyerick, 1911) (Ochromolopis), comb. n. hitherto Epermenia praefumata